JEAN JACQUES ROUSSEAU - ÎNTRE IDEOLOGIA POLITICĂ ŞI ORIGINEA PEDAGOGICĂ - USM ADMIN (Moldova State University, 2007)
Rousseau represents a perfect ideologist regarding the common concepts of natural freedom of men, social contract and his original interpretation makes him a forerunner of left modern politics. Having in sight his main concepts, Rousseau emphasizes the evil pole (represented by the corrupted society) and the good pole (represented by the free individual). Any evil issue comes from weakness and the weakness generates hate. Therefore, the individual cannot be the source of the evil, being as a matter of fact a victim of the society.